2020
DOI: 10.3201/eid2609.202126
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile in COVID-19 Patients, Detroit, Michigan, USA, March–April 2020

Abstract: We describe 9 patients at a medical center in Detroit, Michigan, USA, with severe acute respiratory syndrome coronavirus 2 and Clostridioides difficile . Both infections can manifest as digestive symptoms and merit screening when assessing patients with diarrhea during the coronavirus disease pandemic. These co-infections also highlight the continued importance of antimicrobial stewardship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 9 publications
(7 reference statements)
1
66
2
5
Order By: Relevance
“…After the recent emergence of highly-virulent types, such as BI/NAP1/027, increased CDI incidence, severity of infection and associated mortality have been reported not only in hospitals but also in LTCFs, where residents are at high risk of CDI for advanced age, previous hospitalization and exposure to antibiotics [27e29]. A very recent retrospective study reported nine cases of co-infection with SARS-CoV-2 and C. difficile in elderly hospitalized patients, all which were treated with antibiotics [30]. Interestingly, Sandhu et al also reported an increase of the rate of CDI from 3.32/10,000 patient-days to 3.60/10,000 patient-days during JanuaryeApril 2020.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…After the recent emergence of highly-virulent types, such as BI/NAP1/027, increased CDI incidence, severity of infection and associated mortality have been reported not only in hospitals but also in LTCFs, where residents are at high risk of CDI for advanced age, previous hospitalization and exposure to antibiotics [27e29]. A very recent retrospective study reported nine cases of co-infection with SARS-CoV-2 and C. difficile in elderly hospitalized patients, all which were treated with antibiotics [30]. Interestingly, Sandhu et al also reported an increase of the rate of CDI from 3.32/10,000 patient-days to 3.60/10,000 patient-days during JanuaryeApril 2020.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The first one in May 2020, reporting CDI with COVID-19 at the Medical Center in Detroit, Michigan, USA. Patients were screened from 11th March to 11th April, 2020, and in 9 cases received antibiotic therapy, presented diarrhea, experienced SARS-CoV-2 infection and were co-infected with C. difficile (Sandhu et al, 2020 ). The authors emphasized that when CDI is present as a co-infection with COVID-19 and the diarrhea persists, therapy can be difficult because of the SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 7 , 8 , 9 , 10 , 11 , 12 In addition, there have been reports of GI bleeding, colitis, acute pancreatitis, and exacerbation of prior GI diseases (inflammatory bowel disease). 12 , 13 , 14 , 15 What follows are key GI findings:…”
Section: Introductionmentioning
confidence: 98%